The usability of digital library at Al-Bukhari library among bachelor of office system management students in UiTM Pahang / Norazlina Abd Rahman, Siti Aishah Muhamad Sakri and Zahrah Zubaidah Omar Faruk Khan - Abd Rahman, Norazlina; Muhamad Sakri, Siti Aishah; Omar Faruk Khan, Zahrah Zubaidah (2012)
Digital library has become an increasingly popular learning approach in higher education institutions due to the rapid growth of Internet technologies. Digital library is not intended to replace the traditional library, but to provide easier service to students or researchers or who ever in searching information from anytime and anywhere. If digital libraries are to achieve their full potential, they need to be usable and used - by people for whom information retrieval is not generally the main goal. This study focuses on the usability of digital library among students of UiTM Jengka, Pahang. The usability was measured based on ISO 9241 Usability Model and Nielson Model. In this study, usability covered four dimensions which were efficiency, effectiveness, satisfaction and learnability. The study found that most of the respondents were agreeable that the digital library at Al-Bukhari Library was usable. The level of usability of digital library at AI-Bukhari Library among the students of Bachelor in Office System Management at UiTM Jengka is high. The effectiveness was the most influencing factor toward the usability of digital library while learnability was the least influencing factor toward the usability of digital library at UiTM Jengka.